If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + h = -12 Solving 7 + h = -12 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + h = -12 + -7 Combine like terms: 7 + -7 = 0 0 + h = -12 + -7 h = -12 + -7 Combine like terms: -12 + -7 = -19 h = -19 Simplifying h = -19
| -6p+8+7p=17 | | 9x+16=6x+4+4x-2 | | 17.9-x=12.8 | | 413=7(-7x-18) | | 4u-13=51 | | 8x/9-6=58 | | a+(-6)= | | 4+9=c^2 | | 12x=19.2 | | Cos(2x+10)=sin(3x-30) | | -7(-10x-5)=455 | | 18-x+24=56 | | 0.8+0.2=1 | | 14x=73.5 | | 12x+24=2x^2+2x | | 6x(x-4y)= | | 18y=7(2y-15)+y | | -9(6x-11)=531 | | 5+(12+c)= | | 12/n=5 | | 328+309= | | -17-(-8)-(-9)= | | -2(-13d-18)+20=-18-17+19d | | 8(1-6x)+2=346 | | 4x+10+3x+6=180 | | 135/105 | | 81/(-9) | | -4-3n+3=23 | | x=218+508 | | 3.6/y=10.8/12 | | 30.99-25= | | 5(8x-8)=440 |